Synthesis, Characterization, and Reactivity of a Hydrido‐ and Imido‐Bridged Dinuclear Ytterbium(III) Complex. (27th April 2022) - Wen, Qingqing; Rajeshkumar, Thayalan; Maron, Laurent; Leng, Xuebing; Chen, Yaofeng
Abstract: The trivalent rare‐earth metal hydrido and imido complexes are of versatile reactivity, and many such complexes have been synthesized. However, no example of a rare‐earth metal complex bearing both hydrido‐ and imido‐ligands has been reported. Herein, we report the first rare‐earth metal complex bearing both hydrido‐ and imido‐ligands, namely a hydrido‐ and imido‐bridged dinuclear ytterbium(III) complex. The complex was synthesized via an unprecedented redox reaction of divalent rare‐earth metal hydrido complex with azido compound. DFT calculation indicated that the N2 release from azido compound in the presence of ytterbium(II) is a kinetically facile process because of the cooperative effects of the two metal centers. The reactivity of the hydrido‐ and imido‐bridged dinuclear ytterbium(III) complex was also explored, which showed the redox, addition and σ‐bond metathesis reactivities. Abstract : A hydrido‐ and imido‐bridged dinuclear ytterbium(III) complex (2 ) was synthesized via the reaction of an ytterbium(II) hydrido complex (1 ) with Me3 SiN3 . This unusual product represents the first example of a rare‐earth metal complex bearing both hydrido‐ and imido‐ligands. DFT calculations indicated that the N2 release from Me3 SiN3 is both kinetically and thermodynamically favorable because of the cooperative effects of the two metal centers.